Alternativas de reducción de quema y venteo de gas asociado en la industria petrolera (2018)
This monograph describes the alternatives to reduce the burning and venting of associated gas, it allows to visualize the energy importance of the associated gas, the environmental aspects linked to the generated atmospheric emissions and the obstacles that prevent its environmental disposition in an economically sustainable way. The processes of burning and venting of gas are studied together with the equipment; In addition, standards and programs for the reduction of sources of gas venting and venting are addressed, which national and international entities have formulated and implemented, as in the cases of Ecopetrol together with the Colombian Petroleum Institute, which in the DI & M directed inspection and maintenance program formulate the leak and vent measurement methodology and possible mitigation methods; internationally, the world bank is presented with the rules for voluntary application for the reduction of gas flaring and venting, which stipulate technical guidelines.